An effective time of use tariffs scheme for residential area in Malaysia - Mohammad Jalani, Sri Nor Hafidah (2018)
Time of Use (TOU) is a tariffs scheme that provides variable rate structure for electricity depending on time of day used. In Malaysia, currently, the TOU scheme is only available for industrial and commercial customers. However, the government has wanted to implement TOU scheme in residential area so that a better load profiling can be obtained in the power system. The changes from block tariff to TOU scheme might be increase the customers’ electricity bill. Besides that, the unsuitable TOU structure and pricing might also cause the utility to lose their profit. Therefore, the main objective of this research is to identify the suitable time structure and pricing that will give beneficial to the utility and customers. The recommendation on appropriate incentives along with the TOU pricing signals to encourage customers to have better management on their consumption will also being considered. Thus, the analysis is beginning with residential customers’ behavior modeling. Next, the information of total electricity bill paid by customers will be determined. Last but not least, the statistical analysis will be used to identify suitable TOU structure and pricing. Therefore, the outcome of this research is an effective TOU scheme that will give beneficial to residential customers (in term o f reduce electricity bill) and utility (in term o f profit).